Komunikasi Personal antara Orang Tua dan Anak dalam Pembentukan Akhlak - Amir Faishol; Ujang Didi (STID DI AL-HIKMAH, 2015)
This study has the objective to determine the form of interpersonal communication between parents and children in moral formation in Depok Jaya RW 03 villages conducted from January 2011 to February 2011. The researchers used a qualitative methodology with descriptive approach. In addition to observations, the researchers also obtained data research through interviews and documentation. Instrument used to obtain data support the writers need is to interview guid (interview guide), a tape recorder, worksheets, and questionnaires. The data obtained from this study is qualitative obtained by using observation, interviews and documentation will be analyzed using logic, while the quantitative data obtained through the questionnaire will be tabulated data from the respondent's answer, then do the description and processing of these data.